Russian Personal Libraries of the Turkestan Region in the Collection of the National Library of Uzbekistan Named after A. Navoi - E. V. Pshenichnaya (Библиосфера)
The article deals with littlestudied issues related to the signs of ownership on the books from Russian personal libraries in the Turkestan region (1967–1917) that were found in the National Library of Uzbekistan named after A. Navoi. The purpose of the article: to determine the character of Russian personal libraries of the Turkestan region in the collection of the National library of Uzbekistan named after A. Navoi and the signs of ownership on their books. The relevance of the research is due to the need to fill in the historiographical gap in the study of Russian personal libraries in Turkestan region. The first results of the work related to identification and attribution of the book signs on some books from the personal libraries of N. V. Dmitrovskiy, N. F. Petrovsky, A. K. Gaines, D. I. Mushketov, P. I. Khomutov, N. A. Burov, K. A. Timayev. The paper presents information about the owners of personal libraries. The author analyzes the owner’s inscriptions, which show that these book collections were formed not only for practical purposes, but also for leisure. The article draws the attention of researchers to the study of privately owned signs as another page in the history of replenishment of the book collections of the National Library of Uzbekistan named after. A. Navoi. Identification and attribution of book signs allowed us to understand better the process related to the movement of the books from the personal libraries of Russian aristocrats, officials and scientists to the Turkestan Public Library. The exemplary analysis of the books allowed us to conclude that bibliophiles of the Turkestan region preferred to use stamps more often, among which there are also “non-special” ones, or to put handwritten owner’s inscriptions on copies.